2024
DOI: 10.3390/ejihpe14030030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Active Break Intervention on Attention, Concentration, Academic Performance, and Self-Concept in Compulsory Secondary Education

Julen Maiztegi-Kortabarria,
Silvia Arribas-Galarraga,
Izaskun Luis-de Cos
et al.

Abstract: (1) Background: Society’s shift to a tech-focused era and has created a hyper-connected, sedentary lifestyle. The purpose of this study is to address two objectives: firstly, to describe and analyze the effects of an active breaks program associated with the learning of curricular content (CF-AB) on levels of attention, concentration, and academic performance (AP); secondly, to examine the relationship between intense physical activity (PA), attention, concentration, academic self-concept, basic psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In young university students, it has been shown that there are aspects that can lead to a reduction in the commitment to daily and planned physical activity (restricted schedules, lack of time and lack of will, among others), which have a greater impact on the female sex. Therefore, programs should also focus on this core population ( Kortabarria and Galarraga, 2021 ). With regard to increasing the level of physical activity at these ages (moderate to vigorous intensity), in accordance with the recommended dose ( Franklin, 2021 ), it could contribute to improving psychological aspects such as self-esteem ( Aloufi et al, 2021 ), the level of intrinsic motivation ( Rodríguez-González et al, 2021 ), the development of emotional intelligence ( Cazalla-Luna and Molero, 2014 ) and even better academic performance ( Nuevo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In young university students, it has been shown that there are aspects that can lead to a reduction in the commitment to daily and planned physical activity (restricted schedules, lack of time and lack of will, among others), which have a greater impact on the female sex. Therefore, programs should also focus on this core population ( Kortabarria and Galarraga, 2021 ). With regard to increasing the level of physical activity at these ages (moderate to vigorous intensity), in accordance with the recommended dose ( Franklin, 2021 ), it could contribute to improving psychological aspects such as self-esteem ( Aloufi et al, 2021 ), the level of intrinsic motivation ( Rodríguez-González et al, 2021 ), the development of emotional intelligence ( Cazalla-Luna and Molero, 2014 ) and even better academic performance ( Nuevo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%